Rheological study and printability investigation of titania inks for direct ink writing process - Dolganov, Aleksei; Bishop, Matthew T.; Chen, George Z.; Hu, Di (Elsevier Ltd, 2021)
Titanium dioxide is widely used in numerous industries and with the newly developed titanium manufacturing technique, referred to as the Near-net-shape Electrochemical Metallisation (NEM) Process, the rapid and precise production of titanium dioxide components is highly sought-after. This manuscript presents the rheological investigation and extrudability tests of titania inks, to establish the improved production of titanium dioxide components via Direct Ink Writing. The extrudability tests indicated that despite an unfavourable increase in viscosity during the high shear rates (dilatancy peaks), the best-performing ink had a weight ratio of 1:0.8:0.1 TiO2:H2O:PEG, and the dilatancy peaks were smoothed out with the addition of 0.1 wt ratio of oleic acid to the ink, dramatically improving the quality of the product. To further improve the green bodies a new printing approach was also introduced, removing the necessity for specialised printing bed, by printing a removable support into the green body and allowing for drying without any cracks and warping.